Enhancing ethical awareness through generative AI literacy: A study on user engagement and competence - Kwon, Jungin (Edelweiss Applied Science and Technology, 2024)
Generative artificial intelligence (AI) enables users to quickly and easily create desired outputs. However, it poses potential risks of social disruption due to biases in the data used to generate such outputs. This study examines whether providing literacy-based guidance on the risks and cautionary aspects of generative AI at the point of user acceptance of its outputs can enhance the user's ethical competence. For the study, participants were divided into an experimental group and a control group. The experimental group received warnings about the risks and considerations of accepting AI-generated outputs before using the AI, while the control group received no such guidance. The results revealed that the experimental group, which was informed of the risks and cautionary aspects, showed significant improvements in ethical awareness across various dimensions, including values, self-efficacy, self-regulation and engagement, and ethics and security. Based on these findings, the study suggests that systematic education on the risks and cautionary aspects of generative AI, alongside the technology’s dissemination, can play a crucial role in addressing social and ethical challenges.